2019
DOI: 10.1016/j.ecl.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Conditions in Transgender Populations

Abstract: Transgender persons face unique burdens of dermatologic conditions related to cutaneous effects of gender-affirming hormone therapy and procedures. Skin diseases in transgender patients often underdiagnosed and underrecognized despite potential for significant impairments quality of life and mental health from skin diseases. We discuss basic pathophysiology, diagnosis and treatment of common skin diseases in the transgender populations. For transmasculine patients, common conditions include acne vulgaris and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
2
32

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 56 publications
(73 reference statements)
0
42
2
32
Order By: Relevance
“…Male pattern hair loss usually occurs within a few years after GHT initiation. 12 A prospective study in 20 TM showed that only one TM developed male pattern hair loss within 1 year after testosterone treatment. 13 Concurrently, the 1-year incidence was 17% in another study of 53 TM.…”
Section: Discussionmentioning
confidence: 99%
“…Male pattern hair loss usually occurs within a few years after GHT initiation. 12 A prospective study in 20 TM showed that only one TM developed male pattern hair loss within 1 year after testosterone treatment. 13 Concurrently, the 1-year incidence was 17% in another study of 53 TM.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary sex characteristic care is preventative care. Trans people's mental and physical health, including prevention of violence, can only be addressed when they can access gender‐affirming care, which provides relief from body dysphoria, depression, and anxiety, 19,21 thus resulting in fewer psychotherapy, urgent care, and emergency needs. Trans feminine people who obtain care that helps them to pass as cisgender women, if this is their goal, are less likely to experience violence 20 .…”
Section: Benefits Of Gender Carementioning
confidence: 99%
“…Research regarding transgender health has dramatically increased, yet there is still significant room for improvement as TGNC individuals are at an increased risk for several health issues (Reisner et al, 2016 ; Ackerley et al, 2019 ; Neblett and Hipp, 2019 ; Yeung et al, 2019 ; Wiepjes et al, 2020 ). A gender inclusive approach in biomedical research is vital to our understanding and treatment of TBI.…”
Section: Introductionmentioning
confidence: 99%